2016
DOI: 10.7314/apjcp.2016.17.3.1519
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and Expression of Matrix Metalloproteinase-2 and 9 from Bone Marrow Mononuclear Cells in Myelodysplastic Syndrome and Acute Myeloid Leukemia

Abstract: Background: Matrix metalloproteinase -2 (gelatinase-A, Mr 72,000 type IV collagenase, MMP-2) and -9 (gelatinase-B, Mr 92,000 type IV collagenase, MMP-9) are key molecules that play roles in tumor growth, invasion, tissue remodeling, metastasis and stem-cell regulation by digesting extracellular matrix barriers. MMP-2 and -9 are well known to impact on solid cancer susceptibility, whereas, in hematological malignancies, a paucity of data is available to resolve the function of these regulatory molecules in bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Consistent with our hypothesis, MMP-2 and MMP-9 increase in response to exogenous BCAAs in the hippocampus of rats 60 and bone Report of the GO terms containing the features PRAM1, FGD3, CEACAM3, and NDRG2 among other genes that mapped to significant features at adjusted value of P < .01 (continued) Original Research OBSTETRICS ajog.org marrowederived cells have been also shown to secrete MMPs. [61][62][63] A similar mechanism for cervical remodeling in TL and PPROM involving bone marrowerecruited cells can be further evidenced by KEGG analysis, in which the osteoclast differentiation pathway is enriched not only in PPROM-PTL comparison (Table 2) but also in TL-PTL (Supplemental Table 3). Osteoclasts are bone marrowederived cells traditionally involved in the degradation of bone matrix 64 and have been described to secrete MMP-2 and MMP-9.…”
Section: Ajogorgmentioning
confidence: 71%
“…Consistent with our hypothesis, MMP-2 and MMP-9 increase in response to exogenous BCAAs in the hippocampus of rats 60 and bone Report of the GO terms containing the features PRAM1, FGD3, CEACAM3, and NDRG2 among other genes that mapped to significant features at adjusted value of P < .01 (continued) Original Research OBSTETRICS ajog.org marrowederived cells have been also shown to secrete MMPs. [61][62][63] A similar mechanism for cervical remodeling in TL and PPROM involving bone marrowerecruited cells can be further evidenced by KEGG analysis, in which the osteoclast differentiation pathway is enriched not only in PPROM-PTL comparison (Table 2) but also in TL-PTL (Supplemental Table 3). Osteoclasts are bone marrowederived cells traditionally involved in the degradation of bone matrix 64 and have been described to secrete MMP-2 and MMP-9.…”
Section: Ajogorgmentioning
confidence: 71%
“…Of these c-Cbl [ 24 26 ], c-Raf [ 24 , 27 29 ], Lyn [ 24 , 28 ], VAV1 [ 26 , 37 , 54 ], and CD38 [ 26 ] have been found partnered in a signalsome that generates a signal that regulates proliferation/differentiation and propels RA-induced differentiation of HL-60 AML cells. Smad2 [ 55 ], MMP9 [ 56 , 57 ] and LCN2 [ 58 ] have been attributed with roles in AML leukemogenesis. HL-60 was included for comparison to the patient samples, and in particular to determine if it shared any signaling signature similarities with AML 94 (Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, it has become evident that, to colonize new tissue, leukaemia cells need to develop a premetastatic niche via extracellular matrix remodelling, which they achieve by releasing MMPs (Shay et al 2015). Studies have confirmed that metalloproteinases, including MMP2 and MMP9, play an important role in the invasion process of various solid tumours by digesting the extracellular matrix barrier (Deryugina and Quigley 2006;Chaudhary et al 2016). Thus in order to minimize treatment-associated mortality, suppression of EMT as well as expression of metalloproteinases may represent a rational alternative strategy for reducing metastatic potential of vimentin.…”
Section: Discussionmentioning
confidence: 99%